Achieving Success Everyday (ASE) Model to Develop Students' Academic Buoyancy - Mawarni, Anisa; Thahir, Andi; Yusuf, Syamsu; Ilfiandra, Ilfiandra (Universitas Islam Negeri Raden Intan Lampung, 2022)
The high academic challenges for high school students make many students unable to adapt to live an academic life. The ability to have academic buoyancy is essential for students to be able to adapt to overcome academic challenges. This study aimed to determine the application of group guidance services using the achieving success everyday model to develop students' academic buoyancy. The research uses a qualitative approach which is specifically directed at the use of the simple case hermeneutic method which describes and comprehensively explains various aspects of a group, and qualitative phenomena (language, text, communication, meaning, and experience). The results of the study show the steps of the Achieving Success Everyday (ASE) Model Group Guidance process to develop academic Buoyancy for Students, which include: 1) Assessment phase 2) Review phase 3) Introduction phase 4) Challenge phase 5) Empowerment and development phase 6) Support phase.